THE INFLUENCE OF LOGISTIC ENGLISH PROFICIENCY TOWARDS WORKING ABILITY OF MARITIME UNIVERSITY ALUMNI - Rahayuningsih, Mahsunah Etik; Winarni, Endra (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2021)
The long-term goal of this research is Logistic English which is needed by maritime students, especially the port management study program, due to they have to master it, especially ESP (English for Special Purpose) Logistics. In addition, many alumni work for foreign shipping companies. This inspires the writer to conduct this research. The study entitled "The Influence of Logistic English Proficiency Towards Working Ability of Maritime University Alumni" was to determine how much influence the Logistics English skills possessed by maritime college students in Semarang. The method used in this study, for the population is maritime school students in Semarang, Indonesia, while the sample is using purposive sampling. This type of research uses causality. Meanwhile, for the instrument testing is the instrument validity test and the reliability test. The data collection techniques used questionnaires, observation, literature study, interviews and documentation. Data processing techniques using editing, scoring and tabulation. The data analysis technique uses multiple regression analysis test and goodness of fit test. While to test the data requirements using the normality test, linearity test and classical assumption test. The main finding in this study is that there is a relationship or influence of “Logistic English Proficiency Towards Working Ability of Maritime University Alumni”. Conclusion There is an influence between AKPELNI, STIMART AMNI, PIP and POLIMARIN, where the result has positive influence.